Pengaruh Likuiditas, Financial Leverage, Margin Laba Kotor, Variabilitas Harga Pokok Penjualan, dan Ukuran Perusahaan terhadap Pemilihan Metode Penilaian Persediaan pada Perusahaan Manufaktur yang Terdaftar di BEI Periode 2015–2019 - Suhartanto, Bagus Iman; Tabrani (Majors Accounting, Faculty of Economics and Business, Universitas Pancasakti Tegal, 2021)
This study aims to determine the effect of liquidity, financial leverage, gross profit margins, variability of cost of goods sold, and firm size on inventory valuation methods on manufacturing companies listed on the IDX. This research is a descriptive study with a quantitative approach. The population in this study were companies that registered on the IDX totaling 169 companies. The sample used in this study is to use data collection techniques (purposive sampling) consisting of 29 companies. This research uses logistic regression analysis method with SPSS Version 22 program. The results showed that liquidity affected the inventory valuation method with a significant value of 0.030, financial leverage had no effect on the inventory valuation method with a significant value of 0.699, the gross profit margin affected the inventory valuation method with a significance value of 0,001, the variability in cost of goods sold did not affect the valuation method inventories with a significance value of 0.502, company size has no effect on the inventory valuation method with a significance value of 0.799.